Different strategies for breaking physical seed dormancy in field conditions in two fruit morphs of Vachellia caven (Fabaceae) - Ferreras, Ana Elisa (2018)
Differences in fruit morphology among or within species might indicate differences in other regenerative traits, such as seed dormancy and germination. In species with physical dormancy (PY), environmental conditions are suggested to be responsible for dormancy break in field. Seeds of Vachellia caven have PY. This species exhibits two fruit morphs highly represented in Córdoba forests, Argentina: one is dehiscent and the other is indehiscent. In this study we performed a burial experiment with the aim to determine if the differences in V. caven fruit morphology were related to different patterns of PY break of their seeds in field conditions. We related these patterns to (1) environmental conditions that could influence the loss of PY, and (2) histological features of the lens zone. Seeds of both morphs exhibited dormancy break within 14 months of the start of the experiment, but with different patterns. The dehiscent morph showed an abrupt percentage of seeds that broke dormancy 14 months after the beginning of the experiment, probably after undergoing environmental changes similar to those suggested by the two-stage softening model. The indehiscent morph showed a gradual increase in seeds that broke dormancy, not clearly related to any of the environmental variables studied. No differences in seed coat structure of the lens zone were observed between morphs. The existence of both morphs could confer the species with higher possibilities of establishing and coping with environmental heterogeneity. Those characteristics contribute to the understanding of the success of this species in open and disturbed environments.